2020
DOI: 10.1021/acsomega.0c01016
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Rice Peptide Oryza Peptide-P60 against Oxidative Injury through Activation of Nrf2 Signaling Pathway In Vitro and In Vivo

Abstract: We previously showed that commercially available rice peptide Oryza Peptide-P60 (OP60) increased the intracellular glutathione levels. This study aimed to evaluate the antioxidant potential of this peptide and assess its mechanism of action. Pretreatment of HepG2 cells with OP60 reduced the cytotoxicity caused by H2O2 or acetaminophen (APAP) (47.7 ± 1.3% or 12.2 ± 1.3% of the cytotoxicity for 5 mg/mL OP60 pretreatment compared to that in H2O2- or APAP-treated groups, respectively; p < 0.01) through the restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In this study, immunofluorescence staining results demonstrated that Nrf2 translocation and accumulation into the nucleus by pretreatment with two BAPs and their combination was augmented, thus facilitated the expression of HO-1. These results are similar to the results of recent studies [29,[36][37][38][39]. We also measured the direct antioxidant effect of two BAPs using DPPH radical scavenging assay to check that two BAPs showed the cytoprotective effect through HO-1/Nrf2 signaling.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, immunofluorescence staining results demonstrated that Nrf2 translocation and accumulation into the nucleus by pretreatment with two BAPs and their combination was augmented, thus facilitated the expression of HO-1. These results are similar to the results of recent studies [29,[36][37][38][39]. We also measured the direct antioxidant effect of two BAPs using DPPH radical scavenging assay to check that two BAPs showed the cytoprotective effect through HO-1/Nrf2 signaling.…”
Section: Discussionsupporting
confidence: 89%
“…Accumulating evidence also suggests that the Nrf2/ARE pathway reduces apoptosis and alleviates the inflammatory response, resulting in a significant improvement in tissue retention and beneficial role in coordination [ 48 ]. It is also reported that oxidative signaling and Nrf2 were tightly linked with cellular responses [ 49 ]. Previous studies have revealed mitoQ exerted its protective effects on diseases like traumatic brain injury [ 24 ], intestinal ischemia reperfusion [ 40 ] and diabetic kidney disease [ 17 ] through regulation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it clearly appears that at 100 µM H2 is able to increase the Nrf-2 protein level more than basal condition (C) even in the presence of H2O2 (Figure 5A and 5C). Recently, Oryza Peptide-P60 (OP60), a commercial rice peptide, has been reported to increase intracellular glutathione levels and the evaluation of the mechanisms underlying the antioxidant potential of this peptide in HepG2 cells suggests that OP60 reduced the oxidant stress induced by H2O2 via the Nrf-2 signaling pathway (Moritani, Kawakami, Shimoda, Hatanaka, Suzaki, & Tsuboi, 2020).…”
Section: H2 and H3 Mediate Antioxidant Activity Through The Nrf-2 Pathway Modulationmentioning
confidence: 99%